Qualitative Analysis about Future of Business to Business Marketing in Pakistan - Muhammad Ali; Dr. Zahid Yousaf (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
e-Marketing is a substantial unit of the improved e-Commerce industry. Today, e-Commerce highly depends on e-Marketing as it includes commercial transactions on online platforms. Similarly, it also offers mutual benefits for all the involved parties. In this regard, the current research focuses on examining the future of Online Business to Business Marketing in Pakistan. The researcher selected a sample of n= 15 employees of advertising agencies working in three major cities. Supported by Media System Dependency Theory, results indicated a brighter future of Online B2B Marketing Pakistan. The participants consider Online Business to Business Marketing having a relative advantage due to greater accessibility, cost-effectiveness, accessibility, and other relevant characteristics. Thus, the researcher concluded that, internet can be a greater choice for the manufactures to expand their visibility and generate more revenue in Pakistan. Bridging the gap between agents and customers regarding the internet concept can help to identify potential opportunities and challenges. Moreover, the expanding advertising opportunities on digital platforms, overall digital marketing can be further improved in a broader context.